2008
DOI: 10.1002/eji.200738113
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Act1, a critical modulator of B cell function, leads to development of Sjögren's syndrome

Abstract: CD40L and B lymphocyte‐activating factor (BAFF), members of the TNF superfamily, play critical roles in B cell survival and activation, and in the regulation of humoral immunity. We previously reported that the adaptor molecule Act1 functions as a negative regulator of CD40‐ and BAFF‐mediated B cell survival. Here we demonstrated that mice deficient in Act1 developed systemic autoimmune disease with histological and serological features of human Sjögren's syndrome (SS), in association with systemic lupus eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 25 publications
3
73
0
Order By: Relevance
“…Act1 was later shown to negatively regulate CD40-and B cell-activating factor belonging to TNF family (BAFF) mediated B-cell survival and autoimmunity. 45,46 Act1 contains two TRAF-binding sites, a helix-loop-helix domain at the N-terminus, and a U-box-like region and a coiled-coil domain at the C-terminus. Importantly, it was recently found that Act1 contains a SEFIR domain in its coiled-coil region at the C-terminus, and therefore, Act1 becomes a member of the SEFIR protein family.…”
Section: Il-17 Signalingmentioning
confidence: 99%
“…Act1 was later shown to negatively regulate CD40-and B cell-activating factor belonging to TNF family (BAFF) mediated B-cell survival and autoimmunity. 45,46 Act1 contains two TRAF-binding sites, a helix-loop-helix domain at the N-terminus, and a U-box-like region and a coiled-coil domain at the C-terminus. Importantly, it was recently found that Act1 contains a SEFIR domain in its coiled-coil region at the C-terminus, and therefore, Act1 becomes a member of the SEFIR protein family.…”
Section: Il-17 Signalingmentioning
confidence: 99%
“…Whereas Act1 interacts with the IL-17R through the carboxy-terminal SEFIR domain, it is recruited to CD40 and BAFFR indirectly, mediated by TRAF3 through the TRAF binding site in Act1. Such delicate regulatory mechanisms may provide a common means to promote balance between host defense to pathogens and tolerance to self (Qian et al 2004(Qian et al , 2007(Qian et al and 2008.…”
Section: Use Of a Cdna Library To Discover The Nf-kb Regulator Act1mentioning
confidence: 99%
“…Already at 3-4 weeks of age these mice showed signs of systemic autoimmunity including hypergammaglobulinaemia (IgGs, IgG1, IgG2a, IgG2b), hyper-IgE and inflammation around the eyes (Figure 4.3) [37,51]. Within a couple of months the mice start to express high levels of anti-nuclear autoantibodies including anti-double-stranded DNA and anti-total histones IgGs antibodies, as well as rheumatoid factor (Figure 4.4a).…”
Section: Act1 Inhibits Systemic Autoimmunitymentioning
confidence: 99%
“…(b) The presence of anti-nuclear autoantibodies was followed by lymphocytic kidney infiltrates and IgGs-immune complex deposition in the kidney glomeruli. Kidneys from 8-month-old Act1-deficient or wild-type littermates were stained with haematoxylin/eosin (H&E; top panel) or by fluorescence-conjugated anti-mouse IgGs (lower panel); 100Â magnification [51]. dsDNA, double-stranded DNA.…”
Section: Act1: a Modulator Of Autoimmunitymentioning
confidence: 99%